2019
DOI: 10.1002/rnc.4861
|View full text |Cite
|
Sign up to set email alerts
|

Orbital stabilization of nonlinear systems via the immersion and invariance technique

Abstract: Summary Immersion and invariance is a technique for the design of stabilizing and adaptive controllers and state observers for nonlinear systems. In all these applications the problem considered is the stabilization of equilibrium points. Motivated by some modern applications, we show that the technique can also be used to solve the problem of orbital stabilization, where the final objective is to generate periodic solutions that are attractive. The feasibility of our result is illustrated by means of some cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…In this article we solve the PFP formulating it as an orbital stabilization problem similar to the one studied in Reference 6—where an extension to the I&I technique 11 originally applied for equilibria stabilization was proposed. We recall that this problem is to generate stable periodic solutions for the nonlinear system x˙=f(x)+g(x)u, with state x2n, input um, with m < 2 n , and g ( x ) being full rank.…”
Section: An Iandi Approach To Orbital Stabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article we solve the PFP formulating it as an orbital stabilization problem similar to the one studied in Reference 6—where an extension to the I&I technique 11 originally applied for equilibria stabilization was proposed. We recall that this problem is to generate stable periodic solutions for the nonlinear system x˙=f(x)+g(x)u, with state x2n, input um, with m < 2 n , and g ( x ) being full rank.…”
Section: An Iandi Approach To Orbital Stabilizationmentioning
confidence: 99%
“…The main contributions of the article are 2‐fold. The new reformulation of the PFP is solved by proposing an extension to the recently developed Immersion and Invariance (I&I) orbital stabilization method reported in Reference 6 and using the Mexican sombrero energy‐shaping construction of Reference 7. The resulting controller is a globally defined static state‐feedback that, without the appeal of any guidance laws, guarantees almost global convergence. The result is applied to the benchmark problem of underactuated marine surface vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a particular case of the framework adopted in the immersion and invariance (I&I) technique, first reported for equilibrium stabilization in [2], and later extended for observer design and adaptive control in [3]. In [25] it has recently been shown that I&I can also be adapted for orbital stabilization, leading to a procedure that contains, as particular case, the VHC designs. The only modification done to the standard I&I technique is in the definition of the target dynamics that now should be chosen possessing periodic orbits, instead of an equilibrium at the desired point.…”
Section: Introductionmentioning
confidence: 99%
“…The only modification done to the standard I&I technique is in the definition of the target dynamics that now should be chosen possessing periodic orbits, instead of an equilibrium at the desired point. A main drawback in both the VHC and I&I methods is that the steady-state behavior cannot be fixed a priori, but depends on the initial states, see [25,Remark 2] for a discussion on this matter.…”
Section: Introductionmentioning
confidence: 99%